Understanding BTS Fan Loyalty: The Role of Fan Value Perspective and Sense of Virtual Community on the Weverse Platform - Graciella Roseane Chandy; Prathivi, Maria Dini Gilang (JURNAL ILMIAH EDUNOMIKA, 2025)
This research aims to analyze the influence of the fan value perspective (functional value, emotional value, and social value) on BTS fan loyalty (ARMY), with sense of virtual community (SOVC) as a mediator. This research was suggested by the phenomenon of increasing use of virtual community platforms such as Weverse, which provides direct access for fans to access various contents, as well as interacting with idols and fellow fans. This research data is collected through an online questionnaire to ARMY who use and join BTS’s Weverse, with a total of 400 respondents calculated using the Slovin formula. The data analysis method uses Partial Least Squares (PLS-SEM) with SmartPLS software. The results of this study indicate that the fan value perspective dimension has a significant influence on SOVC, which mediates the influence on fan loyalty. This study provides theoretical contributions to the development of literature related to virtual communities and fan loyalty, as practical implications for the entertainment industry, especially in building fan engagement and loyalty through digital platforms. Keywords: Fan Value Perspective, Fan Loyalty, Sense of Virtual Community (SOVC)